The relationship of the human will and destiny (Journal of Philosophy Culture and Political Science, 2015)
Thinkers of all times in different ways considered the problem of human will and predestination, and the question arises whether or not a person is free in his actions and it all depends on his fate.In this paper system is considered a problem of human will and destiny, the relationship of the two categories in the worldview of the Islamic currents - Kadar. Qadariyah believes that man is free in his actions, and his actions does not depend on the fate and Dzhabarity assume that everything that happens around on the will of God and man must obey them.The purpose of this paper reveal outlook and views on the problem of will and predestination.
Keywords: will; destiny; duty; Ihtiyar; iztirari; predestination.